2009
DOI: 10.1099/vir.0.016899-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus RNA replication is regulated by Ras-Erk signalling

Abstract: The hepatitis C virus NS5A protein has been previously demonstrated to partially attenuate activation of the Ras-Erk signalling pathway, via a conserved class II polyproline motif located towards the C terminus of the protein. However, the role of Ras-Erk signalling in the virus life cycle remains undetermined. To investigate this, levels of RNA replication were measured in genotypes 1 and 2 transient luciferase subgenomic replicon systems in the context of either pharmacological or genetic (dominant-negative)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…This was consistent with the work of Gretton and colleagues, who used SGR-luc-JFH-1, a genotype 2a HCV replicon encoding firefly luciferase, to represent HCV replication (24). They used two types of Ras/Raf/MEK pathway inhibitors and a MEK1 dominant mutant to inhibit this pathway and found a reduction in HCV replication after inhibition (24). However, another study has shown that inhibition of the Ras/Raf/MEK pathway enhances the replication of the HCV subgenomic replicon (29).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This was consistent with the work of Gretton and colleagues, who used SGR-luc-JFH-1, a genotype 2a HCV replicon encoding firefly luciferase, to represent HCV replication (24). They used two types of Ras/Raf/MEK pathway inhibitors and a MEK1 dominant mutant to inhibit this pathway and found a reduction in HCV replication after inhibition (24). However, another study has shown that inhibition of the Ras/Raf/MEK pathway enhances the replication of the HCV subgenomic replicon (29).…”
Section: Discussionsupporting
confidence: 77%
“…According to the results, we concluded that the Ras/Raf/MEK pathway facilitates HCV replication. This was consistent with the work of Gretton and colleagues, who used SGR-luc-JFH-1, a genotype 2a HCV replicon encoding firefly luciferase, to represent HCV replication (24). They used two types of Ras/Raf/MEK pathway inhibitors and a MEK1 dominant mutant to inhibit this pathway and found a reduction in HCV replication after inhibition (24).…”
Section: Discussionsupporting
confidence: 75%
“…NF-κB and MAPKs act as major inflammatory transcriptional factors that bind to consensus sequences on pro-inflammatory genes such as COX-2 and promote their expression48. Previous studies indicate that NF-κB- and MAPKs-mediated COX-2 activation may be used by some viruses such as HCV to promote viral replication49. In our previous study, we observed that potential agents inhibited HCV replication by inhibiting COX-2 expression or activation5051.…”
Section: Discussionmentioning
confidence: 96%
“…activity is required for HCV RNA replication, but complete inhibition of the Ras-ERK signaling is inhibitory (25). Other groups also reported that inhibition of MEK/ERK signaling enhanced HCV propagation (26).…”
Section: Ns5a Interacts With Abi1 and Regulates Mek/erk Signalingmentioning
confidence: 99%